Metaphoric Perceptions of Imam Hatip High School Students Regarding Imam Hatip High School, Vocational Course Teacher and Administrators - Karateke, Tuncay (Cumhuriyet Univ, Fac Theology, 2019)
This study aims to determine the perceptions of Imam Hatip High School students regarding Imam Hatip High School, Imam Hatip High School Vocational Course Teacher and Imam Hatip High School Administration via metaphors. In the study, phenomenological design, one of the qualitative research designs, was used. The study group, which was determined by criterion sampling, which is one of the purposive sampling methods, consists of 412 students studying in 9th and 12th grades in 5 different Imam Hatip High Schools in 2018-2019 academic year. The data of the study were collected from the participants by completing these sentences: Imam Hatip High School is like ... because ..., Imam Hatip High School Vocational Course Teacher is like ... because ... and Imam Hatip High School Administration is like ... because .... The Inductive content analysis technique was used to identify the metaphorical language in the analysis of the data obtained. Themes/categories created as a result of content analysis were analyzed in frequency, percentage, and cross-table in SPSS program. According to the research, it was determined that students' perceptions regarding Imam Hatip High School and Imam Hatip High School vocational Course Teacher were positive; on the other hand, the perceptions regarding the Imam Hatip High Administration were negative. Besides, the metaphoric perceptions of male students, students who graduated from imam hatip secondary school and 9th-grade students were determined to be more positive.
I?mam hatip lisesi öğrencilerinin I?mam hatip lisesi, meslek dersi öğretmeni ve I?darecilerine I?lişkin metaforik algilari
Keywords: Religious Education; Metaphor; Imam Hatip High School; Imam Hatip High Student; Imam Hatip High School Administrators; Imam Hatip High School Vocational Course Teacher